Policy makers’ perceptions and attitudes regarding incorporation of traditional healers into the national health care delivery system - MG Pinkoane (Curationis, 2008)
Based on mixed perceptions which were both negative and positive the policy makers have not been vocal about the process to incorporate traditional healers into the National Health Care Delivery System of South Africa. Negative views were related to the denial that traditional healing does provide a cure and the positive views were identified in the passing of policies from 1994. These policies passed initiated recognition of the existence of traditional healers, but failed to address the important aspect of incorporating the traditional healers into the National Health Care Delivery System. It is these mixed perceptions as well as lack of appropriate policy to facilitate incorporation of traditional healers that urged the researcher to explore the perceptions and attitudes of policy makers regarding this incorporation process, as well as their views on how it should be achieved.